2020
DOI: 10.1002/ange.202005381
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Immobilization Strategy for Dirhodium(II) Carboxylate Catalysts for C−H Functionalization and Their Implementation in a Packed Bed Flow Reactor

Abstract: Herein we demonstrate ap acked bed flow reactor capable of achieving highly regio-and stereoselective CÀH functionalization reactions using an ewly developed Rh 2 (S-2-Cl-5-CF 3 TPCP) 4 catalyst. To optimize the immobilized dirhodium catalyst employed in the flowr eactor,w es ystematically study both (i)t he effects of ligand immobilization position, demonstrating the critical factor that the catalyst-support attachment location can have on the catalyst performance, and (ii)s ilica support mesopore length, dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“… In another example, with a tethered rather than grafted catalyst, Rh 2 (trifluoro­acetate) 4 was complexated to SBA-15 derivatized with amino (APTES) groups either alone or in combination with carboxylic ligands; the latter was clearly superior for the promotion of the cyclopropanation of styrene with ethyl diazoacetate . More subtle but also important is the position at which the ligand bonds to both the linker used for tethering and the immobilized metal ion-ligand: for instance, it has been possible to tune the regio- and stereo-selective of C–H functionalization reactions using a tethered chiral Rh 2 (S-ortho-Cl-(1,2,2-triarylcyclo­propane carboxylate) 4 catalyst by varying the ligand immobilization position . A similar effect related to the point of tethering within the molecular functionalities can be seen with non-metallic organic groups, as illustrated in the examples shown in Figures and . , It is interesting that in those studies it was found that the enantioselectivity of the thiol addition to 2-cyclohexen-1-one decreases not only upon tethering of the cinchona alkaloid catalyst to a silica surface but also if physical mixtures of the homogeneous catalyst with pure silica are used; this is a case where the acid sites of the support independently promote undesirable side reactions (the non-enantioselective coupling of the reactants) .…”
Section: Immobilization Of Homogeneous Catalysts On Surfacesmentioning
confidence: 98%
“… In another example, with a tethered rather than grafted catalyst, Rh 2 (trifluoro­acetate) 4 was complexated to SBA-15 derivatized with amino (APTES) groups either alone or in combination with carboxylic ligands; the latter was clearly superior for the promotion of the cyclopropanation of styrene with ethyl diazoacetate . More subtle but also important is the position at which the ligand bonds to both the linker used for tethering and the immobilized metal ion-ligand: for instance, it has been possible to tune the regio- and stereo-selective of C–H functionalization reactions using a tethered chiral Rh 2 (S-ortho-Cl-(1,2,2-triarylcyclo­propane carboxylate) 4 catalyst by varying the ligand immobilization position . A similar effect related to the point of tethering within the molecular functionalities can be seen with non-metallic organic groups, as illustrated in the examples shown in Figures and . , It is interesting that in those studies it was found that the enantioselectivity of the thiol addition to 2-cyclohexen-1-one decreases not only upon tethering of the cinchona alkaloid catalyst to a silica surface but also if physical mixtures of the homogeneous catalyst with pure silica are used; this is a case where the acid sites of the support independently promote undesirable side reactions (the non-enantioselective coupling of the reactants) .…”
Section: Immobilization Of Homogeneous Catalysts On Surfacesmentioning
confidence: 98%